2005
DOI: 10.1086/491737
|View full text |Cite
|
Sign up to set email alerts
|

Growth in Cecal Mucus Facilitates Colonization of the Mouse Intestinal Tract by Methicillin‐ResistantStaphylococcus aureus

Abstract: Intestinal colonization by methicillin-resistant Staphylococcus aureus (MRSA) is common in some groups of hospitalized patients and has been associated with an increased risk of staphylococcal infection. We tested the hypothesis that growth of MRSA in the colonic mucus layer is required for establishment of intestinal colonization. Mice treated with oral streptomycin before oral administration of MRSA developed persistent intestinal colonization, and the cecal mucus layer contained high concentrations of MRSA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Macfarlane et al (50), who examined the role of the mucus layer coating the human large intestine, have concluded that intestinal bacterial populations growing on mucin surfaces are distinct from their planktonic counterparts present in the gut lumen, in particular in terms of colonization. Consistent with this, it has been observed that inoculating the methicillin-resistant Staphylococcus aureus into the colonic mucus layer leads to rapid bacterial growth, facilitating the intestinal colonization of mice (24). In the same way, Campylobacter jejuni utilizes the secreted MUC2 mucin as an environmental cue for modulating the expression of genes with various functions including colonization and pathogenicity (75).…”
Section: Vol 78 2010 Atypical Epec Benefits From Mucin Elicitation 933mentioning
confidence: 72%
“…Macfarlane et al (50), who examined the role of the mucus layer coating the human large intestine, have concluded that intestinal bacterial populations growing on mucin surfaces are distinct from their planktonic counterparts present in the gut lumen, in particular in terms of colonization. Consistent with this, it has been observed that inoculating the methicillin-resistant Staphylococcus aureus into the colonic mucus layer leads to rapid bacterial growth, facilitating the intestinal colonization of mice (24). In the same way, Campylobacter jejuni utilizes the secreted MUC2 mucin as an environmental cue for modulating the expression of genes with various functions including colonization and pathogenicity (75).…”
Section: Vol 78 2010 Atypical Epec Benefits From Mucin Elicitation 933mentioning
confidence: 72%
“…With an aim to expand the application potential of these strains, it was envisaged that determination of the adhesion potential of the strains to the ECM would be pertinent, as adhesion to ECM molecules such as collagen and mucin is considered as a cardinal feature of probiotic strains (Lebeer et al, 2008). The ability of the pathogen S. aureus to colonize the intestine in conjunction with its ability to adhere to ECM molecules is a serious healthcare concern and has been reported to be responsible for various ailments (Acton et al, 2009;Bhalla et al, 2007;Foster et al, 2014;Gries et al, 2005;Hansen et al, 2006). In this context, probiotic LAB strains having a propensity to adhere onto the ECM such as collagen and mucin could bear interesting therapeutic potential to prevent invasion of the ECM by S. aureus.…”
Section: Resultsmentioning
confidence: 99%
“…The food isolates of L. plantarum used in the present study were earlier characterized as potent plantaricin A producers displaying activity against the target bacteria S. aureus MTCC 96, L. monocytogenes Scott A and E. faecalis MTCC 439 (Singh et al, 2012a). Literature reports suggest that these target bacteria are known to colonize the ECM and are implicated in disruption of ECMrelated barrier functions (Gries et al, 2005;Singh et al, 2012b;Flemming & Ackermann, 2007). As the bacteriocin plantaricin A produced by the L. plantarum strains exhibited profound activity against the target bacteria S. aureus MTCC 96, L. monocytogenes Scott A and E. faecalis MTCC 439 (Singh et al, 2012a), it was envisaged that treatment with plantaricin A would likely result in a significant loss of viability of these bacterial strains, which in turn would curtail their ability to adhere to and colonize the ECM.…”
Section: In Vitro Inhibition Of S Aureus Adhesion To Ecm By L Plantmentioning
confidence: 99%
See 1 more Smart Citation
“…As S. aureus is associated with intestinal colonization (1, 8, 16, 28, 61), adheres to intestinal mucus (70), and is an efficient biofilm former, there is great potential that it exhibits a biofilm phenotype while colonizing this site. Additionally, previous research has demonstrated the importance of the cecal mucus layer, within the intestinal tract of the mouse, in providing a key niche facilitating intestinal colonization by S. aureus (23). Furthermore, the intestinal tract is considered a key location where S. aureus acquires antibiotic resistance genes (59,64), and intestinal colonization further increases the spread and carriage of S. aureus via a fecal- e The position of the first base of the predicted regulatory sequence in relation to the start codon at ϩ1.…”
Section: Discussionmentioning
confidence: 99%